Estudo etnofarmacológico, fitoquímico e biológico de Poikilacanthus glandulosus (Nees) Ariza - Brum, Thiele Faccim de (2016)
Poikilacanthus glandulosus is a subshrub distributed in Southeast and South of Brazil, Paraguay, Argentina and Uruguay and belongs to Acathaceae family. The aim of this study was to perform a phytochemical study and investigate the biological activities of the extracts obtained from the leaves and twigs of P. glandulosus. The plant material was collected in the city of Santiago, RS, Brazil, and is deposited in the herbarium of the Department of Biology UFSM cataloged under the registration numbers SMDB 12.442 and 13.178. The material was macerated in ethanol (70%) and filtered. After, a part of the hydroalcoholic extract (HE) was reserved and the other evaporated in rotary evaporator to remove ethanol (aqueous extract - AE). This was partitioned in ampoules of separation using increasing polarity solvents: dichloromethane (CH2Cl2), ethyl acetate (AcOEt) and butanol (BuOH), being the crude extract (CE) obtained by drying the AE. Through ethnopharmacological study it was possible to collect data on the species with the users of the plant for medicinal purpose, such as popular name, medical use, kind of extract, among others. Phytochemical study revealed the presence of triterpenoids and steroids, coumarins, catechins, phenols, organic acids, amino groups, anthocyanins, anthocyanidins and flavonoids, anthocyanin glycosides, cardioactive glycosides. HPLC analysis revealed the presence of gallic acid in all fractions tested (leaves and branches). Furthermore, the presence of maslinic acid uvaol, sitosterol and α-amyrin species in the extracts was revealed. The CE of leaves showed anti-inflammatory activity and antiedematogenic in vivo. The extracts of leaves showed no cito and genotoxicity at the concentrations tested. The AcOEt fraction showed the highest content of polyphenols and flavonoids in the leaves and the branches of P. glandulosus. In the evaluation of the antioxidant capacity, the AcOEt fraction of branches and CE of leaves were highlighted in relation to inhibition by DPPH radical. The fractions AcOEt of the leaves and CH2Cl2 of branches significantly reduced lipid peroxidation compared to other fractions. In relation to test DCFH, the CH2Cl2 fraction of leaves and branches stood out. In evaluating the antimicrobial activity, the extracts showed good activity against Gram-positive bacteria and were practically inactive against Gram-negative bacteria. Promising activity against the mycobacterium M. smegmatis was found for the CH2Cl2 fraction. The CE and the AcOEt fraction of P. glandulosus leaves decreased biofilm formation formed by S. aureus and CE of branches front S. mutans and L. monocytogenes. The crude extract of leaves and branches presented efeito escolicida contra Echinococcus ortleppi em um curto período de tempo. Through this study, was possible validate the information about medicinal use of P. glandulosus, identify the phytochemical composition and evaluation of biological activities for the first time.